Calibration and accuracy improvement of miniaturized optical system for in-situ roughness measurement - Fu, Shaowei (2016)
In engineering and manufacturing fields, the surface must be under certain limits of roughness to ensure proper functionality and performance. Therefore, measuring surface roughness is vital to quality control in manufacturing industry. This study is first to develop an in-situ measurement system able to calculate a surface roughness value by using a laser confocal displacement meter. In the later experiments, a roughness standard set with various machining processes and a set of gauge blocks were chosen for roughness measurement and calibration. In addition, a high precision stylus profilometer was used as a reference equipment. A series of surface roughness and step height measurements by using laser confocal displacement meter and stylus profilometer are conducted. With the data collected from the measurements, the comparison analysis and calibration will be conducted respectively. Then, the error compensation formulas will be provided to improve the roughness measurement accuracy of the laser confocal system.